Model test of negative Poisson's ratio cable for supporting super-large-span tunnel using excavation compensation method - Manchao He; Aipeng Guo; Zhifeng Du; Songyuan Liu; Chun Zhu; Shiding Cao; Zhigang Tao (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
In recent years, there is a scenario in urban tunnel constructions to build super-large-span tunnels for traffic diversion and route optimization purposes. However, the increased size makes tunnel support more difficult. Unfortunately, there are few studies on the failure and support mechanism of the surrounding rocks in the excavation of supported tunnel, while most model tests of super-large-span tunnels focus on the failure characteristics of surrounding rocks in tunnel excavation without supports. Based on excavation compensation method (ECM), model tests of a super-large-span tunnel excavation by different anchor cable support methods in the initial support stage were carried out. The results indicate that during excavation of super-large-span tunnel, the stress and displacement of the shallow surrounding rocks decrease, following a step-shape pattern, and the tunnel failure is mainly concentrated on the vault and spandrel areas. Compared with conventional anchor cable supports, the NPR (negative Poisson's ratio) anchor cable support is more suitable for the initial support stage of the super-large-span tunnels. The tunnel support theory, model test materials, methods, and the results obtained in this study could provide references for study of similar super-large-span tunnels.